2020
DOI: 10.4067/s0718-34292020000100047
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance of lettuce cultivars in different seasons and shading conditions

Abstract: The objectives of this study were to evaluate the agronomic performance of nine lettuce cultivars (Gloriosa,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
1
1
1
2
Order By: Relevance
“…However, when analyzing the SS treatment, the above premise was not met. The results obtained for the CS and FS treatments were consistent with the results published in previous investigations [52][53][54][55] but these do not coincide with the result of the SS treatment. In Figure 12, the blue arrows mark the trend of radiation, and the orange arrows mark the trend of expected production.…”
Section: Discussionsupporting
confidence: 85%
“…However, when analyzing the SS treatment, the above premise was not met. The results obtained for the CS and FS treatments were consistent with the results published in previous investigations [52][53][54][55] but these do not coincide with the result of the SS treatment. In Figure 12, the blue arrows mark the trend of radiation, and the orange arrows mark the trend of expected production.…”
Section: Discussionsupporting
confidence: 85%
“…These values are higher than those reported by Ferreira et al (2021), who obtained mean commercial fresh mass of 222.71 and 250.70 g plant -1 , with the most productive cultivars when evaluating six cultivars of American lettuce. Likewise, the mean obtained with Dora is higher than that reported by Carini et al (2020), who, evaluating American lettuce cultivars in the autumn-winter period in Santa María, Rio Grande do Sul, Brazil, mention that the Gloriosa cultivar with fresh mass between 530.76 and 547.81 g plant -1 was the most productive. An experiment carried out by Yuri et al (2017) in Petrolina, Pernambuco, Brazil, reported that in the same period in which this research was carried out Volumen 36 (2024) BIOAGRO N° 1…”
Section: Shade Colorcontrasting
confidence: 57%
“…Suboptimal temperatures can have a serious effect on crop yield, with temperatures too low allowing no plant growth and too high causing heat stress and crop spoilage [ 24 , 25 ]. Different varieties necessitate slightly different conditions, and certain seasons may be more appropriate than others, especially as lettuce varieties exhibit diverse behaviours, particularly obvious when exposed to too high temperatures and solar radiation [ 26 ]. Despite this, the ecological requirements for lettuce are fairly forgiving, yet its physiology is still significantly influenced by growing conditions.…”
Section: Discussionmentioning
confidence: 99%